Parenting Mediates the Effects of Income and Cumulative Risk on the Development of Effortful Control. Issue 3 (27th December 2013) - Lengua, Liliana J.; Kiff, Cara; Moran, Lyndsey; Zalewski, Maureen; Thompson, Stephanie; Cortes, Rebecca; Ruberry, Erika
Abstract This study tested the hypothesis that the effects of income and cumulative risk on the development of effortful control during preschool would be mediated by parenting. The study utilized a community sample of 306 children (36–40 months) representing the full range of family income, with 29 percent at or near poverty and 28 percent lower income. Two dimensions of effortful control (executive control and delay ability) were assessed at four time points, each separated by nine months, and growth trajectories were examined. Maternal warmth, negativity, limit setting, scaffolding, and responsiveness were observed. Above the effects of child cognitive ability, income, and cumulative risk, scaffolding predicted higher initial levels of executive control that remained higher across the study, and limit setting predicted greater gains in executive control. Parenting did not predict changes in delay ability. Significant indirect effects indicated that scaffolding mediated the effects of income and cumulative risk on growth in executive control. The findings suggest that parenting behaviors can promote effortful control in young children and could be targets of prevention programs in low‐income families.